Substance use among Ghanaian adolescents in secondary education: the determinants and medico-social implications - Walter Appati; Easmon Otupiri; Adelaide Appati; Eliezer Bernard Owusu Ntim (BMC Public Health)
Abstract Background A significant canker that has been with us for some years now and continues to be on the ascendency, especially among the youth in Ghana, is the use of substances. Adolescence is a period where adolescents tend to indulge in various behaviours, including substance use, as a result of vulnerability to societal influences. Methods A cross-sectional descriptive study was carried out in the New Juaben Municipality, Ghana, to ascertain the determinants of substance use and its medico-social implications on selected second-cycle students. Two hundred and forty (240) students between 12 and 19 were sampled to participate in the study and interviewed using interviewer-guided pretested questionnaires. Results The mean age for substance use was found to be 17.80 years. The majority began substance use as early as between 16–18 years (79.5%). The males (67.5%) indulged in substance use more than the females (32.5%). Most of the students have used alcohol before (53.2%), followed by marijuana (wee) (19.2%) and tobacco (cigarette) (10.9%). Curiosity (53.9%) and peer influence (33.3%) are the main factors driving substance use initiation among students. Majority (39.7%) of students experienced an inability to study for tests, while 29.5% got into fights under the influence of substances. However, the majority (78.2%) of students affirmed their willingness to receive help if addicted to any substance. Conclusion Establishing peer groups and counselling units in secondary institutions can provide crucial support for students, particularly those struggling with addiction, mitigating potential medical and social consequences.